2002
DOI: 10.1021/la020446o
|View full text |Cite
|
Sign up to set email alerts
|

Micropatterning of Block Copolymer Solutions

Abstract: Submicron patterns of block copolymers were generated using an elastomeric mold against solutions of block copolymers. To prevent the swelling of the elastomeric mold by the solvent used in the block copolymer solution, a thin layer of amorphous fluorinated polymer was coated on the surface of the mold. The comparison of patterns generated using an unmodified mold with those generated using a modified mold is also reported. Coupled with their microphase separation at nanometer scale, these block copolymer patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 16 publications
0
36
0
1
Order By: Relevance
“…Flow of a block copolymer solution down an inclined substrate can also orient thick films containing about 10 layers of cylinders [125]. A stamp made from an elastomeric mold pressed into a block copolymer solution on a solid substrate creates a flow field which has the potential for aligning the block copolymer [234]. Recently, Angelescu et al have demonstrated that single layers of molten cylinders can be aligned by shear.…”
Section: Field-induced Ordermentioning
confidence: 99%
“…Flow of a block copolymer solution down an inclined substrate can also orient thick films containing about 10 layers of cylinders [125]. A stamp made from an elastomeric mold pressed into a block copolymer solution on a solid substrate creates a flow field which has the potential for aligning the block copolymer [234]. Recently, Angelescu et al have demonstrated that single layers of molten cylinders can be aligned by shear.…”
Section: Field-induced Ordermentioning
confidence: 99%
“…For example, Teflon-modified PDMS stamps have been employed to pattern block copolymers from solution. [41] Continuous block-copolymer thin films can be molded by, and annealed within, rigid templates to form ordered arrays. [42] With careful control of interfacial properties and molding processes, contact molding can provide a convenient method to pattern polymer films from solution as well as from the melt.…”
Section: Contact Moldingmentioning
confidence: 99%
“…To drive in-plane long-range order of spherical and cylindrical microdomains in thin films, lithographically defined grooved substrates, [77][78][79][80][81][82][83][84][85][86][87][88][89] soft PDMS stamps, [41,90] and hard imprint molds [42] have been used as templates to impose lateral confinement. In-plane cylinders line up along the edges of the templates.…”
Section: Spherical and Cylindrical Microdomains In Narrow Templatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several interesting perspectives are opened by this novel catalyst system: the size of the catalyst domains as well as their spacing are tunable via the composition of the polymer, opening a way of controlling the spacing and possibly the diameter of the tubes. Moreover, patterned, microstructured deposition of this particular block copolymer has already been demonstrated either by soft-lithographical methods [36] or by graphoepitaxy, [31,37,38] adding the possibility to control the location of growth to the above system. The results also seem especially interesting if the use of the PS±PFS system as etch mask for reactive-ion etching (RIE) processes is borne in mind; the possibility of combining substrate structuring followed by CNT growth seems exciting since the growth catalyst will in these cases already be ideally positioned at the top of the structures, eliminating the need to deposit catalysts onto delicate structures.…”
mentioning
confidence: 99%